Identification of the elementary bodies of Chlamydia trachomatis in the electron microscope by an indirect immunoferritin technique. - Ashley, C R (1975)
An indirect immunoferritin (IIF) technique is described for recognizing the elementary bodies (EB) of Chlamydia trachomatis in unsectioned preparations. Both the EB of a genital strain of C. trachomatis grown in irradiated McCoy cells and EB in clinical specimens obtained from patients attending a venereal disease clinic were identified by the IIF test in the electron microscope. Cell culture-grown EB were detected by ferritin staining for up to 4 weeks after the organisms had lost their infectivity for tissue cultures. The IIF test was of comparable sensitivity to isolation methods in detecting chlamydiae in clinical specimens. Other possible applications of the IIF technique are discussed.